2013
DOI: 10.1128/jvi.02078-12
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin Inhibitors Block Arterivirus Replication by Interfering with Viral RNA Synthesis

Abstract: e Virus replication strongly depends on cellular factors, in particular, on host proteins. Here we report that the replication of the arteriviruses equine arteritis virus (EAV) and porcine reproductive and respiratory syndrome virus (PRRSV) is strongly affected by low-micromolar concentrations of cyclosporine A (CsA), an inhibitor of members of the cyclophilin (Cyp) family. In infected cells, the expression of a green fluorescent protein (GFP) reporter gene inserted into the PRRSV genome was inhibited with a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 55 publications
2
58
0
Order By: Relevance
“…also reported that EAV replication was inhibited by knockdown of CypA expression, but not by knockdown of CypB expression [33]. The titers of virus progeny decreased approximately fourfold in CypA-knockdown cells as compared to those in the non-targeted cells.…”
Section: Eav Replication Depends On Cypamentioning
confidence: 98%
See 2 more Smart Citations
“…also reported that EAV replication was inhibited by knockdown of CypA expression, but not by knockdown of CypB expression [33]. The titers of virus progeny decreased approximately fourfold in CypA-knockdown cells as compared to those in the non-targeted cells.…”
Section: Eav Replication Depends On Cypamentioning
confidence: 98%
“…The used virus may have been one of the naturally CsA-resistant viruses that are sometimes present in the virus pool. Several other RNA viruses require CypA or CypB in the replication process, as has been described for HCV, equine arterivirus (EAV), Japanese encephalitis virus, VSV, and West Nile virus (WNV) [16,17,33,34,35]. Therefore, de Wilde et al .…”
Section: Csa Inhibits the Replication Of Diverse Covsmentioning
confidence: 99%
See 1 more Smart Citation
“…The list of these viruses includes flaviviruses and coronaviruses (5,71). HCV usurps the cytosolic CypA to facilitate the assembly of the HCV VRC through influence on the cleavage of the NS5A-NS5B fusion protein and the folding of the NS5A and NS5B RdRp proteins (59,(72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%
“…Downregulated chaperones include HSP90B1 [56], peptidyl-prolyl cis-trans isomerase A (PPIA) [5760] and chaperonin containing TCP1, subunit 2 (Beta) (CCT2) [61,62]. These proteins are downregulated at t2, possibly related to the positive action of GC in proteasome activity and protein turnover [63,64].…”
Section: Discussionmentioning
confidence: 99%